Digitizing rape culture: Online sexual violence and the power of the digital photograph. (April 2016) - Dodge, Alexa
The damaging effects, for both the victims and perpetrators, of photographing sexual assault should be self-evident. However, in the cases of Rehtaeh Parsons, Jane Doe and Audrie Pott, photographs of sexual violence seem to have been taken and digitally disseminated without regard for the possible consequences. Thus, these cases pose disturbing questions about the ways that sexual violence is normalized and legitimized in western culture and the ways that new media is implicated in this process. These cases demonstrate how the ubiquity and permanence of digital photographs create new concerns for victims of sexual violence and new questions regarding the interpretive matrix of photographs. Using Judith Butler's theory on photography, torture and framing, I argue that these cases are an example of what Butler refers to as the digitalization of evil . Through this framework, I will discuss the ways that new media exacerbates experiences of sexual violence and examine issues surrounding the interpretation of photographs of sexual violence.